FAKTOR - FAKTOR YANG MEMENGARUHI PERMINTAAN SAYUR PAKCOY HIDROPONIK DI PASAR GLUGUR RANTAU PRAPAT LABUHANBATU - Pasbon Siburian; Yudi Triyanto; Khairul Rizal; Siti Hartati Yusida Saragih (Fakultas Pertanian, Universitas Janabadra, 2024)
This experiment was aim to investigate some factor influenced by demand for pakcoy hydroponic on glugur rantauprapat labuhanbatu. This research is research using quantitative and descriptive methods. The sampling method used was the accidental sampling method, namely determining the sample based on the coincidence of meeting 30 people with the researcher. The results of the research show that price and population have a positive and significant effect on demand for hydroponic pak choy vegetables in the Gelugur market in Rantauprapat City. It can be seen from the value of the coefficient of determination that demand can be explained by price and population by 76.2%. Meanwhile, the remaining 23.8% was influenced by other variables not examined in this research. Keywords: price, population, demand, hydrophonic, pakcoy